The clinical application of high-resolution peripheral computed tomography (HR-pQCT) in adults: state of the art and future directions - van den Bergh, J.P.; Szulc, P.; Cheung, A.M.; Bouxsein, M.; Engelke, K.; Chapurlat, R. (Osteoporosis international, 2021)
High-resolution peripheral computed tomography (HR-pQCT) was developed to image bone microarchitecture in vivo at peripheral skeletal sites. Since the introduction of HR-pQCT in 2005, clinical research to gain insight into pathophysiology of skeletal fragility and to improve prediction of fractures has grown. Meanwhile, the second-generation HR-pQCT device has been introduced, allowing novel applications such as hand joint imaging, assessment of subchondral bone and cartilage thickness in the knee, and distal radius fracture healing. This article provides an overview of the current clinical applications and guidance on interpretation of results, as well as future directions. Specifically, we provide an overview of (1) the differences and reference data for HR-pQCT variables by age, sex, and race/ethnicity; (2) fracture risk prediction using HR-pQCT; (3) the ability to monitor response of anti-osteoporosis therapy with HR-pQCT; (4) the use of HR-pQCT in patients with metabolic bone disorders and diseases leading to secondary osteoporosis; and (5) novel applications of HR-pQCT imaging. Finally, we summarize the status of the application of HR-pQCT in clinical practice and discuss future directions. From the clinical perspective, there are both challenges and opportunities for more widespread use of HR-pQCT. Assessment of bone microarchitecture by HR-pQCT improves fracture prediction in mostly normal or osteopenic elderly subjects beyond DXA of the hip, but the added value is marginal. The prospects of HR-pQCT in clinical practice need further study with respect to medication effects, metabolic bone disorders, rare bone diseases, and other applications such as hand joint imaging and fracture healing. The mostly unexplored potential may be the differentiation of patients with only moderately low BMD but severe microstructural deterioration, which would have important implications for the decision on therapeutical interventions.